Integrated pest management practices for rice crops: Review of Indonesia and Taiwan - Husnawati Yahya; Kwok-Ching Wong; Ping-Shih Yang (Syiah Kuala University, 2012)
One of the new strategies to control rice pests that are at the same time more environmentally friendly is integrated pest management (IPM). IPM employs such methods as biological and mechanical controls, and botanicalpesticides. National and international resources have been used to developed IPM programs in some countries. Indonesia and Taiwan have used such programs to control rice pests. Biological control, botanical pesticides andsome mechanical control have been conducted in IPM program in both countries. However, assessing and comparing the effects of IPM programs are difficult because of the heterogeneity of the data due to differences in regions (e.g., climate, rainfall, soil structure), time periods, pest classes (e.g., insects, plant pathogens, weeds), and types of crops researched. In Indonesia using the recommended pesticides still be the last option for controlling the pests that reach an economic threshold. In 2011, recommended pesticides are applied about 981,628 ha of all rice crops. Other controls are the second pests control choosen in Indonesia. Other controls are consists of biological control (usingparasitoids and predators), microbial control (fungi, virus and bacteria) and natural plant extraction. Other controls reach about 464,854 ha of total rice crops in Indonesia. Mechanical controls are less applied than recommendedpesticides and other controls. Mechanical controls are including all controls before rice planting, such as harrowing land, killing rats, applying organic fertilizer, planting good varieties and cropping pattern. Mechanical controls reach about 84,920 ha of total rice crops in Indonesia. Taiwan also have similar development of rice IPM like Indonesia. In different counties, the farmers applied different IPM techniques. More farmers are independent to set up their rice pest control. Now, Taiwan have a significant progress in organic rice